1977
DOI: 10.1103/physreva.15.479
|View full text |Cite
|
Sign up to set email alerts
|

Negative-muon capture in ionic compounds and some related elements

Abstract: Relative muon capture probabilities for the individual elements of compounds and relative muonic x-ray intensities have been measured for a series of ionic solids and some related elements. Marked similarities are observed in relative K and L series intensities of a single ionic species. independent of bond partner (eg. Cl in NaCl and CaCI 2 ). However. significant K series differences are observed for an element in an ionic versus a covalent situation (eg. Cl in NaCl and in NaC10 4 ), with the higher K x-rays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In general, it has been found that the modified statistical distribution gives better agreement with the data than the statistical model, but even the former does not always lead to good agreement [6,11,12]. Condo [233 has observed that the modified statistical distribution with the same value of c~ should not be expected to fit both the relative and absolute X-ray yields, since only one parameter is available to allow for a variety of effects, such as distribution over n, uncertainty on the refilling rate and molecular effects.…”
Section: The Angular Momentum Distributionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, it has been found that the modified statistical distribution gives better agreement with the data than the statistical model, but even the former does not always lead to good agreement [6,11,12]. Condo [233 has observed that the modified statistical distribution with the same value of c~ should not be expected to fit both the relative and absolute X-ray yields, since only one parameter is available to allow for a variety of effects, such as distribution over n, uncertainty on the refilling rate and molecular effects.…”
Section: The Angular Momentum Distributionmentioning
confidence: 97%
“…It is usually concluded that the refilling is instantaneous or, at least, rapid in comparison with the cascade time [3,11,12] and that the refilling rate in insulators is not significantly different from the rate in metals. In particular, von Egidy and Povel [3] obtained good agreement with X-ray data for mylar by assuming very fast refilling.…”
Section: Refilling Of Depleted Electron Statesmentioning
confidence: 99%
“…A(Z1, Z2)=Za/Z2 (1) where Z 1 and Z2, in our case, are the atomic numbers of the chlorinated element and chlorine, respec-0340-2193/81/0300/0253/$02.00 [13] et al [14] et al [15] et al [16] et al [17] et al [18] et al [11] or also, calculated in closed form, a weaker dependence [12], the latter being…”
Section: Introductionmentioning
confidence: 99%
“…The dominant uncertainties were the measurement uncertainty in the atomic capture fraction of ±7% (see Ref. [21] for details) and the normalization uncertainty in the muonic x-ray calibration of ±15% (see Ref. [11] for details).…”
Section: Line Intensitiesmentioning
confidence: 99%
“…the fraction of muon stops in NaCl that undergo atomic capture on Cl, was taken from Ref. [21] 1 . The factors C ab and C sv accounted for photon absorption in the target and selfvetoing by the suppressor (C ab varied from 1.02 to 1.03 and C sv varied from 1.06 to 1.16).…”
Section: Line Intensitiesmentioning
confidence: 99%